2018
DOI: 10.1055/a-0734-5609
|View full text |Cite
|
Sign up to set email alerts
|

Neurografie des N. Suralis

Abstract: ZusammenfassungDie Neurografie des N. suralis hat große Bedeutung in der Diagnose von Polyneuropathien. Dieser Artikel stellt unterschiedliche Untersuchungstechniken mit ihren Vor- und Nachteilen vor, bespricht Messergebnisse und Normalwerte und nennt Anhaltspunkte für die Unterscheidung des axonalen und demyelinisierenden Läsionstyps. Letztlich wird ein Standard für die neurografische Untersuchung und deren Bewertung vorgeschlagen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 77 publications
0
3
0
2
Order By: Relevance
“…“ Data collection ”). In instances where one of the first two measurements were invalid due to TE or the first two subsequently collected measurements were deemed strongly discrepant (difference > 10m/s or > 2µV) or as implausible (≥ 60 m/s) 7 , a third or fourth measurement per leg was carried out. Additionally, based on the POCD’s manual 8 , a SNAP of 0µV could also be a TE.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…“ Data collection ”). In instances where one of the first two measurements were invalid due to TE or the first two subsequently collected measurements were deemed strongly discrepant (difference > 10m/s or > 2µV) or as implausible (≥ 60 m/s) 7 , a third or fourth measurement per leg was carried out. Additionally, based on the POCD’s manual 8 , a SNAP of 0µV could also be a TE.…”
Section: Methodsmentioning
confidence: 99%
“…This examination can be performed with orthodrome or antidrome neurography, as it has been shown that nerves conduct electrical signals in both directions equally 6 . The technique of orthodrome neurography consists of applying the stimulating electrode behind the Malleolus lateralis and registering the signal 12-15cm proximally from the stimulation and laterally from the Achilles tendon 7 .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, it was uncertain whether or not its reliability was sufficient for consecutive assessments and clinical follow-up of DPN progression. [36] Novel therapies in the treatment and management of diabetic neuropathy:…”
Section: Novel Targets For Potential Therapeutic Use In Diabetes Mell...mentioning
confidence: 99%
“…Die Konsequenzen daraus, z. B. für Diagnosekriterien, sind noch keineswegs in's allgemeine Bewusstsein gedrungen [6].…”
Section: Anatomie Und Physiologieunclassified
“…Eine einfache Überlegung zeigt, dass der Mechanismus der kollateralen Aussprossung bei diesen zuverlässig über lange Zeit verhindert, dass die PNP durch motorische Neurografie nachweisbar wird. Die sensible Neurografie wäre theoretisch empfindlicher, leidet aber unter einer weit schlechteren Reproduzierbarkeit und äußerst breit gestreuten Normwerten [6]. So ist theoretisch zu erwarten, dass viele Patienten mit PNP normale neurografische Befunde aufweisen.…”
Section: Befundungunclassified